Iowa RBA, October 16, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for October 16, 1995. Highlights of the update include sightings of juvenile Sharp-tailed Sandpiper, Yellow Rail, Red-necked Grebe, Surf Scoter and a Sabine's Gull. Also included are handwritten notes for the next week's update with sightings of an American Pipit and a Horned Grebe. Epson - sheet feed/flatbed